Taxonomy and distribution of species of the genus Acanthus (Acanthaceae) in mangroves of the Andaman and Nicobar Islands, India - P RAGAVAN; ALOK SAXENA; P M MOHAN; R S.C JAYARAJ; K. RAVICHANDRAN (Society for Indonesian Biodiversity, 2015)
Ragavan P, Saxena A, Mohan PM, Jayaraj RSC, Ravichandran K. 2015. Taxonomy and distribution of species of the genus Acanthus (Acanthaceae) in mangroves of the Andaman and Nicobar Islands, India. Biodiversitas 16: 225-237. A recent floristic surveyrevealed the occurrence of three species of Acanthus in mangroves of the Andaman and Nicobar Islands, India. Of these Acanthusilicifolius and A. ebracteatus are shrubs, whereas A. volubilis is a climbing shrub. All the three Acanthus species were recorded from theAndaman Islands, but only A. ilicifolius from the Nicobar Islands. A. volubilis is easily distinguished from other two species by itsunarmed and twining delicate sprawling stems, un-serrated elliptical leaves, white corolla and absence of bracteoles. A. ilicifolius and A.ebracteatus are differentiated based on the presence and absences of bracteoles, corolla color, and position of Inflorescence anddirection of stem axial spines. A key for the species of Acanthus of the Andaman and Nicobar Islands is also provided.